Dentist Communication with the Dental Laboratory for Prosthodontic Treatment Using Implants - Zahra Afsharzand, DMD;1 Behnoush Rashedi, DMD, MSEd, MS;2 (Journal of Prosthodontics, 2006)
A questionnaire was sent to U.S. dental laboratories to evaluate the level of communication between dentists and laboratory technicians and to determine trends in procedures and materials used in fixed and removable implant restorations.